EMPRÊGO DE INSETICIDA SISTÊMICO NO CONTRÔLE DE ALGUMAS PRAGAS DO FEIJOEIRO - Gallo, Domingos; Silveira Neto, Sinval (REVISTA DE AGRICULTURA, 2015)
EMPRÊGO DE INSETICIDA SISTÊMICO NO CONTRÔLE DE ALGUMAS PRAGAS DO FEIJOEIRO